Emergency Medicine as a Medical Speciality in Nigeria: Challenges and Prospects - Wahab Yinusa (Nigerian Postgraduate Medical Journal)
Emergency medicine (EM) globally is a new medical speciality when compared with traditional medical specialities such as surgery, obstetrics, gynaecology and internal medicine. It is a medical speciality that deals with the management of acute illnesses and injuries in a timely and result-oriented manner. The International Federation of EM defines it as a field of practice based on the knowledge and care required for the prevention, diagnosis and management of acute and urgent aspects of illness and injury, affecting patients of all age groups with a full spectrum of episodic, undifferentiated physical and behavioural disorders. Two types of EM are recognised: the out-of-hospital emergency medical services (OHEMS) and the in-hospital emergency medical services (IHEMS). OHEMS was introduced into the country in 1998 by the Lagos state government. IHEMS had been in place for much longer, but it was practised in a heterogeneous and substandard manner. The result of the latter is a casualty department with an overwhelming burden of patients and a high mortality rate. The World Health Assembly (WHA) resolution 60.22 of 2007 mandated every member state government to establish and monitor integrated EM care systems; it is therefore expected that the emergency medical services (EMS) in the country would wear a new look. However, anecdotal reports suggest that both OHEMS and IHEMS in the country are rudimentary and there is no strong evidence to show that EM is embraced by all as a medical speciality. The objective of this study is to examine the challenges and prospects of EM as a medical speciality in Nigeria. A review of the past literature searched in Google, Google Scholar, PubMed and African Journal online was conducted. A total of 40 relevant publications in addition to the authors knowledge and exposure in EM supported the information presented in this manuscript. Our study revealed that inadequate funding and ambulance services, nonavailability of trained bystanders, limited infrastructure and skilled manpower, inadequate and inequitable distribution of health resources, lack of standard emergency department, high out-of-pocket expenses and substandard implementation of EMS policies, are factors militating against a functional EMS in the country. In line with the philosophy of WHA resolution72.16 of 2019, it is recommended that the central government should put in place a mechanism for full and sustainable implementation of the NHIA Act (2022), National Emergency Medical Services and Ambulance System (NEMSAS) and the patient’s bill of rights and direct the adoption of EM as a medical speciality in all federal and state hospitals. In addition, the central government should create public awareness, improve road networks, provide funding, and establish collaboration with local and international organisations.